ADS653 : Principles of public finance / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (2023)
This course gives an in-depth understanding of the components of public finance. The various government financial activities pertaining to revenue collections and expenditure in general which include taxes administration, public debt, procurement, accounting and auditing and their effects on the economy will be examined. The course will also emphasis on the issues of control of funds, accountability, transparency and integrity in public financial administration.